Cultural Divergence in Psychedelic Use among Medical Students: An ESPAD-Adapted Survey among Poles and Iraqis - Ahmed Al-Imam; Marek A. Motyka; Michal Michalak (MDPI AG, 2024)
Psychedelics can profoundly alter cognition and consciousness. Their use in Middle Eastern countries, including Iraq, is ambiguous. We aim to investigate psychedelic awareness and use among Iraqi and Polish medical students. We surveyed 739 university students from Poland (315) and Iraq (424) using 31 adapted questions from the European School Survey Project on Alcohol and Other Drugs (ESPAD). We conducted multivariable analyses based on binary logistic regression to identify the factors associated with psychedelic awareness and use. Most of the respondents were females (65.6%) and senior medical students (69.6%). Notably, the Polish students displayed a higher prevalence of psychedelic use (21.6% compared to 1.2%, p < 0.001), while the Iraqi participants exhibited a lower familiarity with psychedelics (p < 0.001). The multivariable model demonstrated a commendable level of statistical accuracy and satisfactorily conformed to the Hosmer-Lemeshow goodness-of-fit test (statistical accuracy = 91.61%, Nagelkerke R2 = 0.488, p-value = 0.848). Several factors emerged as correlates of increased psychedelic use, including lacking an intact religious belief system or commitment to its practice (OR = 7.26, 95% CI [2.33, 22.60]). Additionally, those who perceived a low risk associated with sporadic psychedelic use (3.03, [1.44, 6.36]) were likelier to engage in such behavior. Other factors included residing in Poland (2.82, [0.83, 9.55]), maintaining positive attitudes toward psychedelics (2.49, [1.20, 5.14]), frequent social nightlife activities (2.41, [1.26, 4.61]), male gender (2.05, [1.10, 3.85]), and cigarette or tobacco smoking (2.03, [1.06, 3.86]). Significant disparities exist between Poles and Iraqis, influenced by religiosity, perceptions of the usage risks, geographical location, gender, attitudes toward psychedelics, parental leniency, and social freedom, especially concerning nightlife activities. Addressing the factors influencing psychedelic usage is paramount to responsible psychedelic engagement and culturally sensitive interventions to prevent misuse.